Perpendicular magnetic anisotropy in Co/Pt multilayers induced by hcp-Ho at 400 °C - Law, Wai Cheung (2021)
In this study, we report that perpendicular magnetic anisotropy (PMA) in Co/Pt multilayers can be achieved by using hcp-Ho(1 0 0) as the seed layer after annealing at 400 °C. M-H hysteresis loops show that the annealing duration required to achieve optimal PMA in Co/Pt multilayers increases monotonically with the Ho seed layer thickness. XRD measurements reveal that Ho transits from amorphous state to hcp structure after annealing at 400 °C, leading to the formation of fcc-Co/Pt(1 1 1). A larger retention of saturation magnetization is also observed when Ho is used as the seed layer as compared to Ru or Pt, which is ascribed to the suppression of interlayer diffusion. This can be attributed to the large grain size of Ho based on the full-width-half-maximum (FWHM) of the Ho peak from XRD results. Synthetic antiferromagnetic (SAF) structures using Ho as a seed layer also demonstrated an exchange coupling strength of Jₑₓ ≈ 1.05 erg/cm² when the thickness of the Ru coupling layer is 0.4 nm.